Intercultural Health Communication in Islamic Medicine among Generation Z - Rita Destiwati; Lucy Pujasari Supratman; Junardi Harahap; Wan Maryam Wan Ahmad Kamil (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
Islamic medical content circulating on social media plays a significant role in shaping Generation Z’s understanding and acceptance of health practices. However, Research on spirituality-based medicine and digital health literacy in shaping Generation Z’s intercultural communication when accessing thibbun Nabawi therapists, religious leaders, or health influencers remains limited. This study aims to explore how spirituality and digital literacy influence Generation Z’s decisions to engage in Islamic medical practices in Indonesia and Malaysia. Employing a comparative qualitative approach, the study involved six Generation Z informants aged 17 to 24, consisting of three participants from Bandung, Indonesia, and three participants from Malaysia, each with prior experience using Islamic medical practices. The findings indicate that Indonesian Generation Z engages with Islamic medicine mainly through family traditions and religious communities, whereas Malaysian Generation Z is influenced by institutional legitimacy and health campaigns integrating religious values with contemporary lifestyles. These results show that Islamic medical literacy extends beyond health behavior to identity formation, spirituality, and meaning making. Therefore, intercultural responsiveness and contextual sensitivity with digital health communication strategies are crucial for improving the effectiveness.Keywords: Intercultural, health communication, generation Z, Islam medical ABSTRAKKonten pengobatan Islam yang beredar di media sosial memainkan peran penting dalam membentuk pemahaman dan penerimaan Generasi Z terhadap praktik kesehatan. Namun, penelitian mengenai pengobatan berbasis spiritual dan literasi kesehatan digital dalam membentuk komunikasi antarbudaya Generasi Z ketika mengakses terapis thibbun Nabawi, tokoh agama, dan influencer kesehatan masih terbatas. Penelitian ini bertujuan untuk mengeksplorasi bagaimana spiritualitas dan literasi digital memengaruhi keputusan Generasi Z dalam menggunakan praktik pengobatan Islam di Indonesia dan Malaysia. Dengan menggunakan pendekatan kualitatif komparatif, penelitian ini melibatkan enam informan Generasi Z berusia 17–24 tahun, yang terdiri atas tiga partisipan dari Bandung, Indonesia, dan tiga partisipan dari Malaysia, yang masing-masing memiliki pengalaman menggunakan pengobatan Islam. Temuan penelitian menunjukkan bahwa Generasi Z di Indonesia lebih banyak terlibat dalam pengobatan Islam melalui tradisi keluarga dan komunitas keagamaan, sedangkan Generasi Z di Malaysia dipengaruhi oleh legitimasi institusional dan kampanye kesehatan yang mengintegrasikan nilai-nilai religius dengan gaya hidup kontemporer. Hasil ini menunjukkan bahwa literasi pengobatan Islam tidak hanya berkaitan dengan perilaku kesehatan, tetapi juga mencakup pembentukan identitas, spiritualitas, dan pencarian makna. Oleh karena itu, responsivitas antarbudaya dan sensitivitas kontekstual dalam strategi komunikasi kesehatan digital menjadi krusial untuk meningkatkan efektivitas.Kata Kunci: Antarbudaya, komunikasi kesehatan, generasi Z, pengobatan Islam